Management control systems and corporate governance: a theoretical review / Palka Chhillar and Pradip Banerjee - Chhillar, Palka; Banerjee, Pradip (Penerbit UiTM (UiTM Press), 2015)
This study presents a systematic review of research on the relationships between various management control system (MCS) components as a package with corporate governance and on their impact on organizational performance. The motivation for the study originates from the past studies who suggested a dearth of research on the configuration and inter-linkages among all components of MCS package: cultural control, planning, cybernetic control, reward and compensation, and administrative control. A thematic approach is followed to conduct a systematic literature review. The review builds upon existing literature and contributes toward identifying research gaps, which may contribute to the existing body of knowledge through theory building and empirical testing.